2009
DOI: 10.1007/978-3-642-03658-3_69
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Brand on the Evaluation of Websites

Abstract: Abstr act. The effect of brand on consumer attitudes towards real and virtual goods is largely documented in consumer psychology and marketing. There is an obvious link between the design of a website and its brand. Yet, this effect has attracted little attention from the HCI community. This paper presents empirical evidence showing that brand attitude influences the evaluation of websites. The effect was reliable across different measures: people holding better attitudes were more positive in the evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Respondents favored matching identity websites and evaluated them more favorably than websites from other religions (both Muslims and Christians); which partially agrees with Siala et al [8] results that only Muslims trusted matching identity websites while Christians favored neutral websites. Brand affected respondents' judgment of content, service quality, usability and aesthetics which agrees with De Angeli et al [4] who demonstrated that people who have positive attitudes towards the website brand were more positive in the evaluation of aesthetics, pleasure and usability. This paper demonstrated clear effects of religion on user judgment of website quality with regards to the websites that has a religious identity regardless of its domain; however, some limitations should be noted.…”
Section: Discussionsupporting
confidence: 86%
“…Respondents favored matching identity websites and evaluated them more favorably than websites from other religions (both Muslims and Christians); which partially agrees with Siala et al [8] results that only Muslims trusted matching identity websites while Christians favored neutral websites. Brand affected respondents' judgment of content, service quality, usability and aesthetics which agrees with De Angeli et al [4] who demonstrated that people who have positive attitudes towards the website brand were more positive in the evaluation of aesthetics, pleasure and usability. This paper demonstrated clear effects of religion on user judgment of website quality with regards to the websites that has a religious identity regardless of its domain; however, some limitations should be noted.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, four of these 11 participants reported that they either owned or used a smartwatch on a regular basis. Given that users' brand familiarity and prior experience are known to affect the evaluation of technology (Langton, Lewis, & Clarkson, ; de Angeli, Hartmann, & Sutcliffe, ), the study excluded responses from these 11 participants and conducted the final data analysis on the responses from the remaining 160 participants (86 males, 74 females, aged 18–30, M = 23, SD = 2.28). A power analysis verified that the current sample size was sufficient for testing the hypotheses, with a power of 87% and medium effect size.…”
Section: Methodsmentioning
confidence: 99%
“…This paper aims at uncovering the logic of how emotional experiences are formed by examining how brand experience affects visual experience. Following the observation that pre-use expectations correlate positively with experiences during the actual interaction (De Angeli, Hartmann, & Sutcliffe, 2009;Raita & Oulasvirta, 2010), the authors hypothesised that brand experience correlates positively with visual experience. This hypothesis was explained with the notion that apperception, which is the process in which meaningful mental representations are formed, depends on previous experiences.…”
Section: Competence and Frustration In Primary Appraisalmentioning
confidence: 99%